Determination of the proportion of total soil extracellular acid phosphomonoesterase (E.C. 3.1.3.2) activity represented by roots in the soil of different forest ecosystems - Rejsek, Klement; Vranova, Valerie; Formanek, Pavel (TheScientificWorldJournal, 2012)
The aim of this study is to present a new method for determining the root-derived extracellular acid phosphomonoesterase (EAPM) activity fraction within the total EAPM activity of soil. EAPM activity was determined for roots, organic and mineral soil. Samples were collected using paired PVC cylinders, inserted to a depth of 15 cm, within seven selected forest stands. Root-derived EAPM formed between 4 and18% of the total EAPM activity of soil from forests of differing maturity. A new approach, presented in this work, enables separation of root-derived EAPM activity from total soil EAPM. Separation of root-derived EAPM from soil provides a better understanding of its role in P-cycling in terrestrial ecosystems. The method presented in this work is a first step towards the separation of root- and microbe-derived EAPM in soils, which are thought to possess different kinetic properties and different sensitivity to environmental change.
Keywords: stromy; ekosystém; Česká republika; Ecosystem; Soil; půda; Trees; Plant Roots; kořeny rostlin; Czech Republic; Phosphodiesterase I; fosfodiesterasa I